Expansión óptima del sistema de transmisión mediante el algoritmo de PRIM - Benavides Larreina, Francisco Patricio (2017)
This article discusses the methodologies that can occur for the expansion of the transmission lines, after the network congestion, taking into consideration the restrictions of the costs. Being hybrids, there are multiple scenarios considering the algorithm of the flow system of generation that can be integrated. The reason for this is because they can be applied to different potency systems. For the Methodology, the minimum expansion is applied to the graph theorems, Krustal and Prim algorithms, the latter being the one used. The IEEE-13 and 30 bus systems will be used on the methodology that will be applied. The decision to expand the transmission network will depend on the sustainable loss that possesses the electrical system, and that determines the growth of the next generation; with the use of technical optimization, the aforementioned systems were modeled with the resolution of potency equations, the creation of minimal expansion trees in order to find the optimization of the potency systems for the transmission network with the Prim algorithm as means.